2016
DOI: 10.1177/2329048x15623548
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Pediatric Neurological Disorders

Abstract: Background: There is no available data from Sudan reflecting the magnitude of the neurological disorders and disabilities in the pediatric age-group. This study aims to evaluate the pattern of neurological disorders among Sudanese children. Patients and Methods: This is a retrospective survey of children with epilepsy and other neurodisability disorders seen at pediatric neurology outpatient clinic, during the period from January 2007 to August 2013. The data of 9600 patients were analyzed. Results: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
(17 reference statements)
2
13
0
Order By: Relevance
“…[1][2][3][4][6][7][8][9] On the contrary, the prevalence rate is similar to the reported prevalence in Sudan. 10 However, a higher prevalence may be obtained from community-based studies as some patients, especially those with myopathies, may be confined to their homes. 5 The addition of disorders whose etiology is from the central nervous system such as cerebral palsy in some of these studies could have also contributed to the higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][6][7][8][9] On the contrary, the prevalence rate is similar to the reported prevalence in Sudan. 10 However, a higher prevalence may be obtained from community-based studies as some patients, especially those with myopathies, may be confined to their homes. 5 The addition of disorders whose etiology is from the central nervous system such as cerebral palsy in some of these studies could have also contributed to the higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The male preponderance is similar to the higher number of males reported in the United Kingdom population of children with NMD. 10 This may be due to the fact that myopathies such as Duchenne muscular dystrophy is inherited in X-linked recessive mode making it mainly expressed in males. However, the male predominance was seen across all the categories of NMDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 It is also known that insufficient or lack of stimulation of the auditory cortex during the allimportant periods of plasticity invariably affects adversely the function of hearing, language and vision development. 4 It has also been found that there is sex predilection among children with neurological disorders with the male sex predominating. 5 Epilepsy and seizure disorders are the commonest neurological disorders seen and managed in most clinics.…”
Section: Introductionmentioning
confidence: 99%
“…We have tried to pay attention to lesser addressed issues of uncommon findings, dysmorphic features, rare diseases [9,10] or chronic neurological problems. [11,12] marked with limited therapy, poor outcome, desperate situation, superimposed with high economic, physical and mental burden to family, along with its detrimental effect on micro economy of the country.…”
mentioning
confidence: 99%